Octopus stew - Velasquez, Eric (Holiday House, 2019)
Ramsey dons his superhero cape to rescue Grandma from the huge octopus she is trying to cook--or is he simply telling a story? Includes author's note on the story's origin and a recipe for Octopus stew.